Fifteen Novel EIF2B1-5 Mutations Identified in Chinese Children with Leukoencephalopathy with Vanishing White Matter and a Long Term Follow-Up - Zhang, Haihua; Dai, Lifang; Chen, Na; Zang, Lili; Leng, Xuerong; Du, Li; Wang, Jingmin; Jiang, Yuwu; Zhang, Feng; Wu, Xiru; Wu, Ye (PLOS ONE, 2015)
Leukoencephalopathy with vanishing white matter (VWM) is one of the most prevalent inherited childhood white matter disorders, which caused by mutations in each of the five subunits of eukaryotic translation initiation factor 2B (EIF2B1-5). In our study, 34 out of the 36 clinically diagnosed children (94%) were identified to have EIF2B1-5 mutations by sequencing. 15 novel mutations were identified. CNVs were not detected in patients with only one mutant allele and mutation-negative determined by gene sequencing. There is a significantly higher incidence of patients with EIF2B3 mutations compared with Caucasian patients (32% vs. 4%). c.1037T>C (p.Ile346Thr) in EIF2B3 was confirmed to be a founder mutation in Chinese, which probably one of the causes of the genotypic differences between ethnicities. Our average 4.4 years-follow-up on infantile, early childhood and juvenile VWM children suggested a rapid deterioration in motor function. Episodic aggravation was presented in 90% of infantile cases and 71.4% of childhood cases. 10 patients died during the follow-up. The Kaplan-Meier curve showed that the median survival time is 8.83 ± 1.51 years. This is the largest sample of children in a VWM follow-up study, which is helpful for a more depth understanding about the natural course.